Factors influencing user intention to buy through multi-service platform (Gojek) in Aceh - Arrie Muhammad Aries Sharief
The new era of smartphone mobile applications in Indonesia has been started since the formation of the GOJEK application in 2010, where Gojek became the first super app or multiservice platform to provide more than 20 services. GOJEK is one of the applications that utilizes technological and economic advancements in Indonesia. GOJEK is a company that provides multiple online services such as transportation, delivery of goods and foods. Since 2016, GOJEK has significantly improve Aceh economy and hopefully it will fix many problems that Aceh has been facing so far. Gojek has made positive impact since the beginning and has become an important main role in SMEs, especially in 2020 since the Covid-19 pandemic began to emerge and based on the Demographic Institute of the Faculty of Economics and Business, University of Indonesia (LD FEB UI) the Gojek survey helps buffed the economy for those whose affected by Covid-19, as many as 40 %t SMEs joined Go-food (one of GOJEK service) and 90% are micro scale business. as many as 92% of SMEs says they were able to adapt in pandemic due to GOJEK and almost 50% say they would not be able to survive if they were not part of the Gojek ecosystem. With statement above this study aims to analyze and provide information on what factors that actually influencing user to buy through Multi-Service Platform (GO-JEK) in Aceh in order to find what are those factors that helps SMEs and other micro small-scale business to thrive in this pandemic. In this quantitative study the samples of the study are gathered using a non-probability sampling technique with 95% confidence level and 8% error margin. The data is collected using survey questionnaires through Google Form. In this study the scale is measured using Likert scale. To test the effect of the independent variable with the dependent variable regression linear method is used, where this model using 4 steps in building mediation. These finding provides future evidence supporting current economic and technology innovation on how these 4 variables influencing Use of Multi-Service Platform (GO-JEK) in Aceh.